A Study of Major Factors Influencing Customer Preference for Branded Coffee Chains among Young and Middle-Aged Adults in Mumbai - John, Jackson; Banerjee, Sanchayita (SFIMAR Research Review, 2017)
The coffee shop industry has been growing rapidly. In India, the branded coffee chain market is highly fragmented, with Café Coffee Day, Costa and Starbucks being few of the leading coffee chain businesses, operating in the country. The aim of this study is to understand the factors that influence customer choice while patronizing branded coffee shops. A quantitative study using a structured questionnaire was conducted with 120 respondents, based in the Greater Mumbai Metropolitan region. The most preferred brand with the surveyed respondents was Café Coffee Day. Majority of them also prefer branded coffee chains over non-branded ones due to many social and motivational factors. A factor analysis was conducted in order to find out the most important factors that influence the customer’s choice of branded coffee shops. Satisfaction level, brand reputation and human behaviour, and marketing tactics, accounted for 60 per cent of the factors that influence the choice of branded coffee chains. The findings of this study provided valuable insights about Indian consumers who have a positive attitude towards consuming branded coffee beverages.